Pelatihan Analisis dan Intepretasi Data Menggunakan Aplikasi Microsoft Excel - Ekaputra, Firdiawan (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2024)
The purpose of this activity is to train data analysis and interpretation based on validation and reliability tests using the Microsoft Excel application. Data analysis and interpretation training activities using the microsoft excel application were carried out in room L-101 FKIP Jambi University which was attended by 20 students. The purpose of this training activity is to improve students' data analysis and interpretation skills using the Microsoft Excel application, so that it is expected to facilitate students in conducting research and improve the quality of student research. Data analysis and interpretation training activities using the Microsoft Excel application consist of three stages of activity, namely the preparation stage, the implementation stage, and the evaluation stage. Based on the training activities that have been carried out, students feel happy with the training activities that have been carried out. Students know the features and benefits of Microsoft excel application more widely. The existence of Microsoft excel application training can be utilized to develop their knowledge.